Comparative study between the influence of processed and unprocessed semen prepared by conventional layering and centrifugation technique in infertile patients after intra-uterine insemination performance - KH. Kouti, Bassim; A. A., Dheia; H. A., Amir (University of Thi-Qar Journal of Science, 2010)
This study was designed to compare the effect of prepared and unprepared semen processed by conventional layering (direct swim-up) and centrifugation swim-up technique on seminal fluid analysis parameters and pregnancy rates in infertile subjects undergoing intrauterine insemination (IUI) performance. Fifty infertile couples enrolled in this study and semen samples were analyzed before and after in vitro sperm activation by standard semen parameters. However, spermatozoa prepared by direct layering technique and centrifugation swim-up technique. Conversely, HOS-test was performed before and after in vitro sperm preparation by mixing 0.1 ml of semen with 1.0 ml of 150 mOsm/L NaCl as a hypo-osmotic solution. Furthermore, sperm concentration, sperm motility, progressive sperm motility, normal sperm morphology, and HOS-test were evaluated according to standard WHO criteria. For IUI technique, sperm prepared and incubated for 30 minute in 5% CO2 at 37ºC. The results of the present study indicate a highly significant (P<0.001) differences for all sperm functions and sperm HOS-test (P<0.001) were reported post in vitro sperm activation using direct swim-up and centrifugation swim-up method as compared to pre-activation. Whereas, the best results for clinical pregnancy rate were reported for semen samples prepare by using simple layering technique with IVF medium.